Antineoplastic effects of nutrient mixture on Raji and Jurkat t cells: the two highly aggressive non hodgkin’s lymphoma cell lines - Roomi, M.W.; Bhanap, B.A.; Roomi, N.W.; Rath, M.; Niedzwiecki, A. (Experimental Oncology, 2009)
Non-Hodgkin lymphomas incidence has increased more than 70% in last 25 years. Aggressiveness, higher relapse rate, and treatment complications pose significant barriers. Decreased food intake and side effects of treatments make cancer patients vulnerable to deficiency of essential nutrients such as vitamin C, lysine, and proline leading to the formation of weak extra cellular matrix susceptible to easy breakdown by matrix metalloproteinase enzymes. Inhibition of these enzymes has shown promise in stopping metastasis. Aim: In this study, we investigated the effects of a specific nutrient mixture, containing ascorbic acid, lysine, proline, green tea extract among others, in most aggressive forms of non-Hodgkin’s lymphoma — Burkitt’s lymphoma, and T-cell lymphoma — using Raji and Jurkat cells respectively. Methods: Nutrient mixture (NM) doses of 0, 10, 50, 100, 500, 1000 μg/ml, were used to study effects on cell proliferation, expression of matrix metalloproteinase, Matrigel™ invasion and apoptosis. Results: The results demonstrated that the dose response toxicity of the nutrient mixture on Raji cells gradually increased with increasing concentration. The nutrient mixture was non-toxic to Jurkat cells, however exhibited anti-proliferative properties at higher concentrations. Zymography demonstrated, NM had a significant inhibitory effect on matrix metalloproteinase-9 expression with total inhibition at 1000 μg/ml for Raji cells and at 500 μg/ml for Jurkat cells. The NM at 100 μg/ml completely inhibited Matrigel ™ invasion for Raji cells, and at 1000 μg/ml for Jurkat cells. After the NM challenge virtually all Raji and Jurkat cells exposed to 1000 μg/ml were in late apoptosis. Conclusion: Considering the lack of treatment options and continually increasing incidence, NM could be further explored for its therapeutic potential in Burkitt’s lymphoma and T-cell lymphoma.